2013
DOI: 10.1111/cns.12125
|View full text |Cite
|
Sign up to set email alerts
|

Octodon degus: A Model for the Cognitive Impairment Associated with Alzheimer's Disease

Abstract: Octodon degus (O. degus) is a diurnal rodent that spontaneously develops several physiopathological conditions, analogous in many cases to those experienced by humans. In light of this, O. degus has recently been identified as a very valuable animal model for research in several medical fields, especially those concerned with neurodegenerative diseases in which risk is associated with aging. Octodon degus spontaneously develops β-amyloid deposits analogous to those observed in some cases of Alzheimer's disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 74 publications
1
39
0
Order By: Relevance
“…These studies highlight the therapeutic potential of the induction of TMS in O. degus. Taking into consideration that this rodent constitutes a "spontaneous" model of neurological disorders such as Alzheimer´s disease (Tarragon et al, 2013), it holds a significant promise to progress in the comprehension of brain mechanisms and to originate novel …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies highlight the therapeutic potential of the induction of TMS in O. degus. Taking into consideration that this rodent constitutes a "spontaneous" model of neurological disorders such as Alzheimer´s disease (Tarragon et al, 2013), it holds a significant promise to progress in the comprehension of brain mechanisms and to originate novel …”
Section: Discussionmentioning
confidence: 99%
“…Analyzing memory impairment caused by this challenge in the O. degus is particularly important and considerable, since this social rodent has become an increasingly familiar and accepted experimental animal in the latest years. Furthermore, many therapeutic and medical disciplines, particularly those referred to brain functions, has characterized as an important animal model for research (Tarragon et al, 2013). We used SD as a condition which alters the formation and expression of memories and originates a failure in both procedural and declarative memories (Walker and Stickgold, 2004) (Jugovac and Cavallero, 2012) (Huber et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been revealed that NFT composed of hyperphosphorylated tau form in the brains of domestic cats, Tsushima leopard cats, and degus, 24,28,187 which cannot be explained by the brain aging speed hypothesis. Table 2 summaries the Ab amino acid sequences of various animals.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…AD, a neurodegenerative disease, is one of the most common and multifactorial forms of dementia characterized by multiple cognitive impairments, personality changes, and abnormal behavior 2 . The key pathological emblems observed in AD brain tissues are amyloid beta (Aβ ) peptide and hyperphosphorylated tau (p-tau) protein, although the exact mechanisms which cause these alterations are yet to be uncovered 3 . The formation of Aβ is due to the aggregation of extracellular senile plaques (SP), while neurofibrillary tangles (NFTs) are caused by abnormal deposits of p-tau proteins 3 .…”
Section: Introductionmentioning
confidence: 99%